Honda Motor's Logos as Superimposed Advertisement Strategy in Opera Van Java Television Program - Erlan Aditya Ardiansyah (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2020)
Abstract A motorbike manufacturer which struggles to market their products is Honda Motor Co., Ltd. (hereinafter referred as Honda Motor). This article investigated origin of Honda Motor’s logos and tried to describe the logos as superimposed advertisement displayed in a television program. The study applied a qualitative descriptive method. Data were taken from a commedy situation Overa van Java relayed on Trans7 television channel. The data are the Honda Motor’s logos displayed as superimposed advertisement. The results showed that Honda has denotation and connotation meanings. The company name was originated from the family name of the founder Soichiro Honda. However, there is also another meaning ‘Japanese rice’ due to marketing strategy which delivers cultural values due to promote Japanese products. The Honda Motor’s logos are a red-colored wing on a white background and a white-colored wing on a red background. The logos are discovered as the signified while the products of Honda Motors become the signifier. The logos slid with approximately 11 seconds of duration which depicted brand awareness. This study concludes that the superimposed advertisement employed mini images on the left corner of a television screen. The advertisement strategy is valuable to cause intention of the television audiences through the signifier and signified. Keywords: Logo, meaning, sign, signifier, signified, superimposed advertisement Abstrak Pabrikan sepeda motor yang berjuang untuk tetap memasarkan produknya adalah Honda Motor Co., Ltd. (selanjutnya disebut Honda Motor). Artikel ini menginvestigasi logo Honda Motor dan mendeskripsikan logo tersebut sebagai iklan superimposed yang ditayangkan dalam program televisi. Penelitian ini disusun dengan menggunakan metode kualitatif. Data diperoleh dari situasi komedi Overa van Java yang ditayangkan pada saluran televisi Trans7. Data yang diperoleh berupa logo Honda Motor yang ditampilkan sebagai iklan superimposed. Hasil penelitian menunjukkan bahwa Honda memiliki makna denotasi dan konotasi. Nama perusahaan berasal dari nama keluarga pendirinya, yaitu Soichiro Honda. Akan tetapi, terdapat makna lain 'beras Jepang' sebagai upaya strategi pemasaran yang memiliki nilai budaya untuk mempromosikan produk dari Jepang. Logo Honda Motor adalah sayap berwarna merah dengan latar belakang putih dan sayap berwarna putih dengan latar belakang merah. Logo-logo tersebut dinyatakan sebagai penanda sementara produk-produk Honda Motor menjadi petanda. Logo-logo ditampilkan saling berganti dengan durasi sekitar 11 detik untuk menyampaikan brand awareness. Penelitian ini menyimpulkan bahwa iklan superimposed menampilkan gambar berukuran kecil di sudut kiri layar televisi. Strategi iklan ini berupaya untuk meningkatkan pemahaman dari penonton televisi melalui penanda dan petanda. Kata Kunci: Logo, makna, tanda, penanda, petanda, iklan superimposed